2011
DOI: 10.1002/jmr.1163
|View full text |Cite
|
Sign up to set email alerts
|

N‐isopropylacrylamide as a functional monomer for noncovalent molecular imprinting

Abstract: Although N-isopropylacrylamide (NIPAM) has previously been used in molecular imprinting, it has mostly been considered as an 'inert' monomer, or included for its temperature-responsive nature, rather than as a functional monomer responsible for the interactions with the template at the recognition site. A comparative study of NIPAM and other traditional, functional monomers for the imprinting of a hydrogen bond donor template, bisphenol A (BPA), is reported. Nuclear magnetic resonance titration data suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The rest of the polymerization mixture, composed of the functional monomer NIPAM, the fluorescent monomer rhodamine B, the cross-linker EbAm and the initiator system (KPS, TEMED) in buffer A, was then passed through the column. NIPAM is a functional monomer capable of hydrogen bond interactions, due to the presence of oxygen and nitrogen atoms 32,33 , but at the same time was used herein as the major component in this polymer recipe to obtain thermoresponsive MIP-NPs. The lower critical solution temperature of the polymer was determined by dynamic light scattering by measuring the particles size versus temperature and found to be ∼32 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the polymerization mixture, composed of the functional monomer NIPAM, the fluorescent monomer rhodamine B, the cross-linker EbAm and the initiator system (KPS, TEMED) in buffer A, was then passed through the column. NIPAM is a functional monomer capable of hydrogen bond interactions, due to the presence of oxygen and nitrogen atoms 32,33 , but at the same time was used herein as the major component in this polymer recipe to obtain thermoresponsive MIP-NPs. The lower critical solution temperature of the polymer was determined by dynamic light scattering by measuring the particles size versus temperature and found to be ∼32 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have also chosen NIPAM 10 as a co-monomer. It is demonstrated that NIPAM usually does not interact with the template in polar solvents as DMSO and water, but acts as a stabilizer of the polymeric structure [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amide group in acrylamide could form stronger hydrogen bonds with the template than the carboxyl group. 13 Crosslinking used etilenglicol dimetacrilat (EGDMA) with molecular formula of C10H14O4 (Mr 198.22; ρ=1.051 gr/mL). EGDMA was one of most often used crosslinker in the synthesis of MIP because it could produce a polymer which has good thermal and mechanical stability; could form a stable polymer; have good porosity and easily polymerized.…”
Section: Synthesis Of Mip and Nip Acrylamidementioning
confidence: 99%